New 5-methylisatin-thiosemicarbazones: preparation, spectroscopic elucidation and antioxidant properties - Bakır, Temel Kan (Springer Science and Business Media LLC, 2024)
Abstract
New isatin-thiosemicarbazone (1–6) were obtained from various 5-methylisatin and various isocyanates with good yields and efficient methods. The structures of the synthesized compounds were clarified by FT-IR, 1H-NMR, and 13C-NMR spectroscopic techniques and elemental analysis. In the study using butylated hydroxytoluene (BHT) as a reference antioxidant, 2,2-diphenyl-1-picrylhydrazyl (DPPH) antiradical quenching capacities of the synthesized compounds were determined. The free radical scavenging effects of the synthesized compounds were compared with the IC50 values obtained from the concentration equations and were found in the order BHT > 6 > 5 > 3 > 2 > 1 > 4. Structural and electronic properties of the compounds were examined by density functional theory (DFT) calculations and their relationship with the antioxidant properties of the compounds was discussed. DFT calculations played an important role in determining how the electronic properties of the synthesized compounds, especially in the presence of different substituents and in the ortho and meta positions, and accordingly the antioxidant properties of the compounds, changed. Experimental and theoretical results confirmed that methoxy-containing structures in the synthesized compounds exhibit higher antioxidant effects compared to halogen-containing structures, regardless of their position.